(untitled) (Revista Contexto & Educação, 2026)
The COVID-19 pandemic highlighted the central role of healthcare professionals as strategic agents in mitigating health crises. Exposed to a high risk of infection, intense emotional overload, and increased responsibilities in promoting public health, they require adequate protection, with vaccination being a fundamental measure to ensure the safety and continuity of health services. Vaccine hesitancy, although a minority, is associated with factors such as misinformation, doubts about the vaccine development process, apprehension regarding vaccine safety, and barriers to access. This study, conducted with 276 professionals from the SES/DF (Health Secretariat of the Federal District), identified a high rate of vaccine adherence (99.3%), despite persistent mistrust related to the speed of vaccine development. A predominance of females was observed in the sample (78.3%), reflecting the composition of the healthcare workforce. The qualitative and quantitative analysis showed that 79.7% of participants reported previous SARS-CoV-2 infection, reinforcing the importance of protective measures, such as the use of personal protective equipment. Furthermore, 47.5% of professionals reported experiencing bereavement during the pandemic. Although vaccine hesitancy was reduced, its presence reinforces the need for continuous health education strategies based on transparency and scientific evidence. Therefore, consistent institutional policies and targeted educational actions are essential to strengthen confidence in vaccination and ensure collective protection within the context of health services.